1994
DOI: 10.1111/j.1476-5381.1994.tb14871.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of salt by a novel potassium‐ and magnesium‐enriched salt alternative improves the cardiovascular effects of ramipril

Abstract: 1The influence of salt (sodium chloride; NaCl) (an additional 6% in the diet) and that of a novel sodium-reduced, potassium-, magnesium-, and L-lysine-enriched salt alternative on the cardiovascular effects of ramipril was studied in stroke-prone spontaneously hypertensive rats in a 6-week study. The intake of sodium chloride was adjusted to the same level by adding the salt alternative at a 1.75 times higher amount than regular salt. 2 Salt produced a marked rise in blood pressure and induced cardiac hypertro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
7
17
0
Order By: Relevance
“…Calcium has been shown to enhance vasorelaxation in experimental trials (Mäkynen et al, 1996;Jones et al, 1997). Potassium and magnesium also have beneficial effects on vascular function (Mervaala et al, 1994;Mäkynen et al, 1995;Tolvanen et al, 1998). On the other hand, the electrolyte concentrations did not differ markedly between the test and placebo drinks.…”
Section: Discussionmentioning
confidence: 91%
“…Calcium has been shown to enhance vasorelaxation in experimental trials (Mäkynen et al, 1996;Jones et al, 1997). Potassium and magnesium also have beneficial effects on vascular function (Mervaala et al, 1994;Mäkynen et al, 1995;Tolvanen et al, 1998). On the other hand, the electrolyte concentrations did not differ markedly between the test and placebo drinks.…”
Section: Discussionmentioning
confidence: 91%
“…The vascular relaxation enhancing effect of ramipril was blocked by regular salt supplementation (34). However, during the salt alternative supplemented diet (sodium chloride intake adjusted to the same level) the vascular relaxation enhancing effect of ramipril was only slightly attenuated (34). Hence, changes in vascular reactivity may also explain the hypertensive effect of sodium chloride and the beneficial effects of potassium, magnesium and /-lysine.…”
Section: Discussionmentioning
confidence: 91%
“…In agreement with these studies, we found recently (34) that in SHRSP ramipril improved vascular relaxation during a low-sodium diet. The vascular relaxation enhancing effect of ramipril was blocked by regular salt supplementation (34). However, during the salt alternative supplemented diet (sodium chloride intake adjusted to the same level) the vascular relaxation enhancing effect of ramipril was only slightly attenuated (34).…”
Section: Discussionmentioning
confidence: 93%
“…Calcium improves vasorelaxation in experimental trials (Jolma et al, 2003;Ma¨kynen, Ka¨ho¨nen, Wu, Arvola, & Po¨rsti, 1996). Potassium and magnesium improve beneficial effects of ACE inhibition on vascular function (Mervaala et al, 1994). The effects of potassium might be mediated by increasing endothelial nitric oxide production (Zhou, Kosaka, & Yoneyama, 2000).…”
Section: Discussionmentioning
confidence: 99%